Auditing Analgesic Use in Post-operative Setting in a Teaching Hospital - Sumana Sen; Prapthi Bathini (Journal of Clinical and Diagnostic Research, 2015)
Introduction: Managing postoperative pain efficiently is one important therapeutic challenge in the hospitals. Combination use of analgesics is in vogue, where in drugs from the opioid and non-opioid group are given synergistically. The aim of this study is to audit the use of different analgesics on the first postoperative day. Effort has been made to look into the drug or drug combinations used and other factors associated with their use. Materials and Methods: Retrospective, cross sectional observational study was conducted over a period of 11 months in a tertiary care teaching hospital at Hyderabad with approval from institutional ethics committee. Medical records of 649 patients on the first postoperative day were analysed for analgesics by various indicators. Results: Average number of drugs per encounter was 4.23. Percentage of patients prescribed drugs from national essential drug list/WHO was 81.94%. Most common analgesic (monotherapy) prescribed was tramadol followed by diclofenac and the most common combination drugs prescribed were tramadol+Paracetamol. The most common route of administration was intravenous. All the drugs except piroxicam, were in the lower limit of the recommended daily dose. Conclusion: The present study gives an idea of the overall pattern of analgesic drug use in postoperative patients. The drug combinations used, the most common single use drug can be made out. The health professionals can be encouraged to prescribe by generic name and from the National List of Essential Medicines NLEMs.